2007
DOI: 10.1016/s1040-2608(07)12009-8
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Contact and Support Within Intergenerational Relationships in the Netherlands: a Cohort and Time-Sequential Perspective

Abstract: This study investigates whether the frequency of contact and support exchanged in relationships between parents and adult children declines over successive cohorts and over individual time in the Netherlands.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 27 publications
0
23
0
1
Order By: Relevance
“…The pressure of combining employment and caregiving responsibilities might lead to less contact and support between older parents and adult children. In the study by van der Pas et al (2007) parents aged 55 to 65 years as well as their children were in 2002 more often employed (40 per cent and 84 per cent, respectively) than parents and their children in 1992 (31 per cent and 72 per cent, respectively). The results showed that parent's and child's (part-time or full-time) employment was not related to contact frequency.…”
Section: Mean Number Of Biological Adult Children According To Varioumentioning
confidence: 96%
See 3 more Smart Citations
“…The pressure of combining employment and caregiving responsibilities might lead to less contact and support between older parents and adult children. In the study by van der Pas et al (2007) parents aged 55 to 65 years as well as their children were in 2002 more often employed (40 per cent and 84 per cent, respectively) than parents and their children in 1992 (31 per cent and 72 per cent, respectively). The results showed that parent's and child's (part-time or full-time) employment was not related to contact frequency.…”
Section: Mean Number Of Biological Adult Children According To Varioumentioning
confidence: 96%
“…In 1990 these percentages were 33 per cent and 22 per cent, respectively. In 2002 a further decline in intergenerational co-residence was observed at 23 per cent and 16 per cent, respectively (van der Pas et al 2007). Considering adults aged 55 years up to 89 years the figures in Table 10.1 indicate that intergenerational co-residence is on a very low level; 6 per cent of the parents co-resides with at least one child.…”
Section: Mean Number Of Biological Adult Children According To Varioumentioning
confidence: 99%
See 2 more Smart Citations
“…Despite a decrease in proximity of children, they observed an increase in contact across cohorts, which can partly be explained by structural factors, such as a decline in family size and improvements in means of communication. Van der Pas et al (2007) examined relationships of young-old parents and their adult children over two successive cohorts in the Netherlands. Parents of the later cohort had more contact and support exchanges with their children than the earlier cohort, revealing that families have not declined in importance.…”
Section: Changing Family Structuresmentioning
confidence: 99%